An Empirical Study of Economic Cycle, Air Quality, and National Health Since Reform and Opening Up - Chai, Kuang-Cheng; Li, Qiang; Bao, Xing-Li; Zhu, Jiawei; He, Xing-Xing (Frontiers in Public Health, 2021)
Since the reform and opening up of China, the economy has continued to grow, and diverse needs have generated different types and periods of economic activities. This has caused people to have an unhealthy diet, lack of exercise, irregular work and rest, lack of sleep, mental stress, high psychological pressure, long-term bad moods, and other health problems. The proportion of the sub-healthy population continues to increase and health problems are becoming increasingly prominent. Based on this, we examine the internal mechanism of the economic cycle on national health since the reform and opening up of China. For a long time, China has actively responded to the UN's call for environmental protection and proposed that “clear waters and lush mountains are invaluable assets.” Therefore, this study combines air quality in the process of environmental governance in China to investigate national health. Data from 22 provinces, five autonomous regions, and four municipalities from 2004 to 2017 are selected as research samples to examine the relationship between economic cycles, air quality, and national health for empirical testing. Studies have shown that the economic cycle is significantly correlated with national health. The better the macroeconomy, the better the health of the human body; that is, the lower the unemployment rate, the lower the mortality rate. After introducing air quality, it was found to have a significant regulating effect on the relationship between the economic cycle and national health. Our conclusions reveal that economic development is closely related to national health. China should attach great significance to the environment and air quality in the process of economic development to achieve sustainable development and create a green economy.